Microstructure evolution and mechanical properties of vacuum brazed ZrO2/Ti–6Al–4V joint utilizing a low-melting-point amorphous filler metal. (October 2021) - Liang, Yuzheng; Kong, Jian; Dong, Kewei; Song, Xinxiang; Liu, Xiangkui; Zhu, Rui
Abstract: The shear strength of ZrO2 and TC4 brazed joint is usually controlled by the oxide reaction layer adjacent to the ZrO2 ceramic. However, there are few studies of the formation and growth mechanism of this reaction layer at present. And the relationship between brazing parameters, joint strength and thickness of the oxide reaction layer also needs further study. In this study, the ZrO2 and TC4 were brazed using a low-melting-point Ti35 Zr25 Be30 Co10 amorphous filler at different brazing parameters. The microstructure and mechanical performance of the joints were studied by SEM, EPMA, XRD, TEM as well as shear tests. The results revealed that the TiO layer was formed on the surface of ZrO2 ceramic, and the joint strength reached the highest value of 180 MPa at 810 °C for 10 min. The formation of the TiO layer is a typical reaction-diffusion process and its growth process exhibits characteristics of an island growth mode. Furthermore, the quantitative relationships between the brazing parameters and the thickness of the TiO layer were established, which paves an innovative way for improving the strength of the joint by controlling the thickness of the TiO layer. Highlights: A low-melting-point Ti35 Zr25 Be30 Co10 amorphous filler was used to join ZrO2 and TC4. High-strength joining of ZrO2 and TC4 was obtained, the shear strength was about 180 MPa. The formation and grow process of the TiO layer was study in detail. The quantitative relationships between brazing temperature, holding time, and the thickness of the TiO layer were established.